2016
DOI: 10.4103/ijmr.ijmr_1486_15
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic abnormalities in cirrhosis & their correlation with severity of cirrhosis using Child-Pugh score among patients in a tertiary care hospital

Abstract: Background & objectives:Child-Pugh score (CPS) is a widely used prognostic marker in cases of cirrhosis and pulmonary arterial hypertension (PAH). However, the role of this score in the quantification of severity of PAH is not well studied. In mild cases, echocardiography is more sensitive. This study was done to assess the association between echocardiography and severity of cirrhosis using CPS.Methods:A cross-sectional study was done from April to June 2014 in 42 patients with cirrhosis using a pre-tested se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
1
2
Order By: Relevance
“…However, TAPSE and parameters of DD correlated with severity of liver disease as seen by natural PELD/MELD score, prothrombin time, INR and decompensated portal hypertension. Evidence of this is in contrast to a study of patients with cirrhosis where no signi cant association was found between echocardiographic changes and Child-Pugh score (25).…”
Section: Discussioncontrasting
confidence: 99%
“…However, TAPSE and parameters of DD correlated with severity of liver disease as seen by natural PELD/MELD score, prothrombin time, INR and decompensated portal hypertension. Evidence of this is in contrast to a study of patients with cirrhosis where no signi cant association was found between echocardiographic changes and Child-Pugh score (25).…”
Section: Discussioncontrasting
confidence: 99%
“…An Indian study reported a very high prevalence of POPH (35.71%). [ 26 ] In our study, the worsening Child scores did not significantly alter the prevalence of POPH, which was in line with the findings of similar studies. [ 26 27 28 29 30 ] High mPAP and PVR during right heart catheterization were diagnostic of POPH.…”
Section: Discussionsupporting
confidence: 93%
“…[ 26 ] In our study, the worsening Child scores did not significantly alter the prevalence of POPH, which was in line with the findings of similar studies. [ 26 27 28 29 30 ] High mPAP and PVR during right heart catheterization were diagnostic of POPH. [ 22 ] 2D echocardiography finding of high right ventricular systolic pressure (>25 mmHg) is also a fairly good indicator of POPH.…”
Section: Discussionsupporting
confidence: 93%
“…The circulatory dysfunction described during cirrhosis responsible for hypovolemia could explain these electrical abnormalities [5] [18]. However, more in-depth studies using holter-ECG combined with plasma calcium measurement will enable a better assessment of the QT interval in cirrhosis patients, as recommended by patients, found no association between echographic cardiac abnormalities and Child Pugh score, in contrast to our findings [14]. Some authors have shown a link between advanced fibrosis and the risk of heart failure and death [24].…”
Section: Discussioncontrasting
confidence: 85%